The Contribution of UP SOLAIR to Labor Empowerment - Sibal, Jorge V. (Philippine Journal of Labor and Industrial Relations, 2021)
This paper discusses the contribution of UP SOLAIR to labor empowerment through education. It focuses in the period 1982 until the elevation and expansion of the School to UP SOLAIR. More than two decades of the past history of the School illustrates the practice of institution-building within an academe. In its recent history, the institution reinvented itself with a graduate program in IR to expand its academic program aimed at labor empowerment, social justice and economic development. The author asserts that labor empowerment and social justice cannot be attained if the country remained un-industrialized. Industrialization and economic development are not tasked to the labor movement alone. It is a collective effort by labor, management, government and the civil society sectors.